Rural infrstructure and regional development in southern Africa - Wanmali, Sudhir; Islam, Yassir (International Food Policy Research Institute, 1997)
Food security refers primarily to the availability of and access to food at the individual, household, village, regional, national, and even global level. It thus encompasses critical aspects of production, consumption, distribution, and trade of food and agricultural commodities. Rural infrastructure is of central importance in facilitating production, consumption, distribution, and trade and is therefore critical in achieving food security in the rural economy. The availability of and access to rural infrastructure by individuals within the rural economy is both necessary and pivotal in the achievement of food security.